2019
DOI: 10.1063/1.5084773
|View full text |Cite
|
Sign up to set email alerts
|

Polymer nucleation under high-driving force, long-chain conditions: Heat release and the separation of time scales

Abstract: This study reveals important features of polymer crystal formation at high-driving forces in entangled polymer melts based on simulations of polyethylene. First and in contrast to small-molecule crystallization, the heat released during polymer crystallization does not appreciably influence structural details of early-stage, crystalline clusters (crystal nuclei). Second, early-stage polymer crystallization (crystal nucleation) can occur without substantial chain-level relaxation and conformational changes. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 48 publications
7
39
0
Order By: Relevance
“…As such, small nuclei are not simply smaller versions of larger-scale crystals, which aligns with insights from previous work monitoring the shape of nascent polymer crystals [38]. Previous work [42] has demonstrated that nucleation in entangled polymer melts at high-driving forces (i.e., for the types of systems considered in this study) is a local event guided by local environments. Nucleation rates for long-and short-chain systems similarly indicate that nucleation is a local event [14].…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…As such, small nuclei are not simply smaller versions of larger-scale crystals, which aligns with insights from previous work monitoring the shape of nascent polymer crystals [38]. Previous work [42] has demonstrated that nucleation in entangled polymer melts at high-driving forces (i.e., for the types of systems considered in this study) is a local event guided by local environments. Nucleation rates for long-and short-chain systems similarly indicate that nucleation is a local event [14].…”
Section: Resultssupporting
confidence: 87%
“…By comparing SDK-based results for molten polyethylene and polyethylene crystallization to results from experiments and atomistic simulations, we have previously demonstrated that the SDK model is an appropriate model for studying polyethylene systems [41]. Due to their coarse-grain nature, molten SDK polyethylene chains diffuse ∼4.07 times faster than those in experimental samples, as discussed in our previous work [41,42]. As such, all simulation times reported in this study correspond to scaled times (i.e., internal LAMMPS times × 4.07), unless otherwise stated, in order to facilitate comparisons with experimental timescales.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations